Pendampingan Penyusunan Laporan Keuangan Pada Mini Market SRC Luthfi di Kelurahan Sidomulyo Barat Pekanbaru Riau - Masril, Masril; Sitinjak, Marnala; Piliang, Arfah; Yusuf, Muhammad (Jurnal Penelitian dan Pengabdian Masyarakat, 2024)
MSMEs play an important role in economic growth. There are several problems faced  by MSMEs at  this  time  including  difficulties  in  marketing,  limited  innovation,and  technology,  as  well  as  limited knowledge about makingfinancial statements. In order to increase interest in the importance of knowledge about financial statements, Thesecommunity service activities are very necessary at this time.The method of devotion is done  by giving  Lectures, Discussions,and Mentoring.As theresults of this activity, MSME actors already understand how to make financial statements, namely balance sheets and income statements